Integration Of Technology In Problem-Based Learning To Improve Students Computational Thinking: Implementation On Polymer Topics - Nurasiah, Nurasiah; Paristiowati, Maria; Erdawati, Erdawati; Afrizal, Afrizal (IJOSMAS, 2023)
This research is motivated by the importance of developing computational thinking skills for students in facing the challenges of the 21st century. Computational thinking is described as a thinking process in formulating problems and solving problems computationally through computers, humans or machines. Its skills can be measured during the learning process of students with the approach of basic computational thinking strategies as follows: Are students able to decompose complex problems into simpler problems? (Decomposition), can students create problem patterns? (Pattern recognition), are students able to focus on issues that are considered important? (Abstraction), and whether students can solve problems systematically (Algorithm) with SMART (specific, measurable, attainable, relevant, time-based). The research aims to improve students' computational thinking skills through the integration of technology in problem-based learning models on polymer topics. This study uses a quasi-experimental quantitative method with none equivalent control group design. The subjects in this study were students of SMAN 1 South Tangerang City, totaling 66 students of class XII. The results showed that the computational thinking skills of students increased after the implementation of the problem-based learning model integrated with technology. This is indicated by the average N-Gain Score for the experimental class which is 56.65%, which is included in the quite effective category, and based on the independent sample t-test. The Sig value is obtained. (2-tailed) 0.007. This indicates Sig. (2-tailed) <, it can be concluded that there is a significant positive effect of the use of technology integration in the problem-based learning model on polymer topics.